2022
DOI: 10.1002/jmd2.12317
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies in Wilson disease: Impact on clinical course

Abstract: Symptoms of Wilson disease (WD) vary and additional factors such as autoimmunity may play an important role in WD pathogenesis. The presence of antinuclear antibodies (ANA), anti‐neutrophil cytoplasmic antibodies, neuronal surface antibodies, and onconeural antibodies in WD was investigated using standardized indirect immunofluorescence assays and Western Blot analysis. The presence of all studied autoantibodies was higher in WD patients in comparison to healthy subjects, but there was no statistically signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…These include ANAs, antiphospholipid antibodies and, rarely, even anti-double-stranded DNA [ 17 , 18 ]. Antczak-Kowalska M et al reported that the presence of all studied autoantibodies was greater in WD patients than in healthy individuals [ 19 ]. The role of autoantibodies in the pathogenesis of WD is unclear but may be related to a bystander phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…These include ANAs, antiphospholipid antibodies and, rarely, even anti-double-stranded DNA [ 17 , 18 ]. Antczak-Kowalska M et al reported that the presence of all studied autoantibodies was greater in WD patients than in healthy individuals [ 19 ]. The role of autoantibodies in the pathogenesis of WD is unclear but may be related to a bystander phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…However, rarely, ocular manifestations with symmetrical ophthalmoparesis (especially horizontal gaze paresis) and rapid-remitting diplopia may occur. In the AChR-Ab MG group, late onset (>50 years of age) is seen most frequently in men, with variable symptoms, including ocular manifestation (diplopia, symmetrical ptosis) and good response to acetylcholinesterase inhibitors (pyridostigmine) [ 16 , 34 , 35 ]. Hence, based on these observations, the phenotype of MG in our patient seems to be related to AChR-Abs, but the presence of both Abs supports us to diagnose the general autoimmune reaction caused by DPA treatment [ 35 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the AChR-Ab MG group, late onset (>50 years of age) is seen most frequently in men, with variable symptoms, including ocular manifestation (diplopia, symmetrical ptosis) and good response to acetylcholinesterase inhibitors (pyridostigmine) [ 16 , 34 , 35 ]. Hence, based on these observations, the phenotype of MG in our patient seems to be related to AChR-Abs, but the presence of both Abs supports us to diagnose the general autoimmune reaction caused by DPA treatment [ 35 , 36 , 37 , 38 ]. However, in the literature, cases of DPA-induced MG without Abs against AChR and MuSK are also described (up to 20% of cases) [ 16 , 18 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations